Correction: Lignin amination valorization: heterogeneous catalytic synthesis of aniline and benzylamine from lignin-derived chemicals. Issue 19 (14th September 2021) - Rong, Yue; Ji, Na; Yu, Zhihao; Diao, Xinyong; Li, Hanyang; Lei, Yaxuan; Lu, Xuebin; Fukuoka, Atsushi
Abstract : Correction for 'Lignin amination valorization: heterogeneous catalytic synthesis of aniline and benzylamine from lignin-derived chemicals' by Yue Rong et al., Green Chem., 2021, DOI: ; 10.1039/d1gc02741g .